BRIDGING PEDAGOGY AND TECHNOLOGY: DEVELOPMENT AND EVALUATION OF A PBL-BASED LKPD ELEKTRONIK TO ENHANCE PROBLEM-SOLVING ABILITY AND SCIENCE PROCESS SKILLS - Indah Kristiani Siringo Ringo; Ayu Annisa Akbar; Olfiane Tamarengki; Andi Nurhidayah; Agrielsa Alphasati Sinaga (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The persistent challenges in developing students’ higher-order thinking skills in science learning indicate that the integration of technology and pedagogy has not been optimally implemented. This study aimed to develop and evaluate a Problem-Based Learning (PBL)-based electronic student worksheet (e-LKPD) in terms of its validity, practicality, and effectiveness in improving students’ problem-solving abilities and science process skills. The study employed a Research and Development (R&D) approach combined with a quasi-experimental design involving experimental and control groups. The research stages included product development, expert validation, limited trials, and implementation in the learning process. The results showed that the developed PBL-based e-LKPD was categorized as highly valid and highly practical based on expert validation and positive user responses. In terms of effectiveness, the experimental group demonstrated greater improvement than the control group, with N-Gain scores of 0.60 for problem-solving ability and 0.50 for science process skills, both categorized as moderate, while the control group obtained scores of 0.29 and 0.27, respectively. Multivariate statistical analysis also confirmed significant differences between the two groups. Although the resulting effect sizes were relatively low, the findings indicate that the integration of Problem-Based Learning into digital learning media provides a positive contribution to improving students’ problem-solving abilities and science process skills in science education. ABSTRAK Rendahnya keterampilan berpikir tingkat tinggi peserta didik dalam pembelajaran sains menunjukkan bahwa integrasi teknologi dan pedagogi belum dilaksanakan secara optimal. Penelitian ini bertujuan untuk mengembangkan dan mengevaluasi lembar kerja peserta didik elektronik (e-LKPD) berbasis Problem-Based Learning (PBL) ditinjau dari aspek validitas, kepraktisan, dan efektivitas dalam meningkatkan kemampuan pemecahan masalah dan keterampilan proses sains peserta didik. Penelitian menggunakan pendekatan Research and Development (R&D) yang dipadukan dengan desain quasi experiment melalui kelompok eksperimen dan kelompok kontrol. Tahapan penelitian meliputi pengembangan produk, validasi ahli, uji coba terbatas, serta implementasi pada proses pembelajaran. Hasil penelitian menunjukkan bahwa e-LKPD berbasis PBL yang dikembangkan berada pada kategori sangat valid dan sangat praktis berdasarkan hasil validasi ahli serta respons positif pengguna. Dari aspek efektivitas, kelompok eksperimen menunjukkan peningkatan yang lebih tinggi dibandingkan kelompok kontrol dengan nilai N-Gain kemampuan pemecahan masalah sebesar 0,60 dan keterampilan proses sains sebesar 0,50 yang termasuk kategori sedang, sedangkan kelompok kontrol memperoleh nilai masing-masing sebesar 0,29 dan 0,27. Analisis statistik multivariat juga menunjukkan adanya perbedaan yang signifikan antara kedua kelompok. Meskipun ukuran efek yang dihasilkan masih relatif rendah, hasil penelitian ini menunjukkan bahwa integrasi Problem-Based Learning dalam media pembelajaran digital mampu memberikan dampak positif terhadap peningkatan kemampuan pemecahan masalah dan keterampilan proses sains peserta didik dalam pembelajaran sains.